Antibacterial biocomposites: efficacy of MWCNT-coated Hanji cellulose paper against E. coli - Mufarah Amjad; Jeong, Yunjo; Shin, Subin; Kim, Bogyeong; Kim, Namyeon; Hyunjin, Cho; Lee, Sang seok; Lee, Sungbi; Na, Won jin; Jang, Se Gyu; Moon, SeonYoung; Lee, Eun-Hee; et al. (Springer, 2024)
Cellulose paper has been studied for its application as an antibacterial filter, due to its robust porous structure, minimal ecological footprint, biocompatibility, and inherent antibacterial properties. Moreover, its properties can be further enhanced via surface functionalization with metallic nanoparticles (NPs) such as silver, zinc, etc. However, the synthesis of metallic NPs is challenging, costly, and environmentally harmful. On the other hand, carbon nanotubes (CNTs) are highly suitable as an additive to cellulose paper due to their high electrical conductivity, excellent mechanical strength, ease of fabrication, and antibacterial properties. In this study, we coated multi-walled carbon nanotubes (MWCNTs) on Hanji, a traditional Korean paper, using a simple dipping method and investigated its antibacterial activity against Escherichia coli (E. coli). The MWCNT-coated Hanji exhibited an inhibition efficiency of？~？93% against E. coli cells. Moreover, the MWCNT coating resulted in improved mechanical strength, enhanced electrical conductivity, and increased hydrophobicity of the Hanji. Furthermore, it was observed that MWCNTs exhibited exceptionally stable adhesion to the Hanji surface. Our finding shows that MWCNT-coated Hanji could be utilized as an antibacterial material that is used as masks, air pollution filters, and wallpapers in hospitals and residential complexes, and an efficient platform for antiviral studies.